2017
DOI: 10.1016/j.jcv.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of seroprevalence of varicella zoster virus: A nationwide population-based study

Abstract: Varicella zoster virus (VZV) causes chicken pox as a primary infection following which it becomes latent in neurons. It may then reactivate to cause shingles (herpes zoster). Severity of lesions and VZV pathogenicity are depended on the host's immune response and variant in VZV Dr Athina Myrto ChioniIdentification of VZV seroprevalance rate in general population may lead to develop new health strategic managements such as vaccination. Therefore, we aimed to provide a systematic review of the seroprevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
2
17
1
2
Order By: Relevance
“…The present study found that a certain proportion of young adults (20-29 years old) was susceptible to varicella. The age-speci c seropositivity of varicella in this study was similar to previous ndings from Spain, Switzerland, and Iran [18][19][20]. The disease burden of varicella in Vietnam is not well known, but varicella is one cause of central nervous system infections in northern [6] and southern Vietnam [7].…”
Section: Mumpssupporting
confidence: 87%
“…The present study found that a certain proportion of young adults (20-29 years old) was susceptible to varicella. The age-speci c seropositivity of varicella in this study was similar to previous ndings from Spain, Switzerland, and Iran [18][19][20]. The disease burden of varicella in Vietnam is not well known, but varicella is one cause of central nervous system infections in northern [6] and southern Vietnam [7].…”
Section: Mumpssupporting
confidence: 87%
“…The incidence of VZV in women was also higher than that in men, and the difference increased with age. Compared with Amjadi et al (Amjadi, 2017), the prevalence rate of VZV in Chinese women was 62.71%, which was lower than that in Iranian women (80.47%). Dong Yanhong et al (Dong, 2017) found that the VZV prevalence of the elderly that was 96.56% in Chaoyang District of Beijing was slightly higher than that of 95.30% in Iran.…”
Section: Figure 4 Forest Plots Of Vzv Prevalence In Different Genderscontrasting
confidence: 73%
“…This study’s findings confirm previous reports that single-dose varicella vaccine is insufficient to provide the population with an immune barrier. Based on varicella surveillance and seroprevalence data, it was found that there was a negative correlation between the reported incidence and seroprevalence among regions, which indirectly indicated that the immunization effect of varicella vaccine could prevent the spread of varicella to a certain extent [ 20 ]. The state of the varicella epidemic is the most serious and the seroprevalence of antibody in children is the lowest in the southern Jiangsu region, meaning that the occurrence of varicella virus infection in this region can easily cause an epidemic outbreak of varicella.…”
Section: Discussionmentioning
confidence: 99%